2006
DOI: 10.1111/j.1365-2036.2006.02982.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and adherence to proton pump inhibitors in daily clinical practice

Abstract: SUMMARY BackgroundProton pump inhibitors are widely used, but little is known about the usage pattern in different indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
82
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 18 publications
5
82
2
4
Order By: Relevance
“…Most of the studies date several years back, have clustered PPI use with use of histamine type-2 receptor antagonists (H2RA) and were not carried out in a nationwide setting. Furthermore, the studies applied different definitions of long-term use, based on either duration of therapy or used defined daily doses (DDDs) per year, without taking both parameters into account [Hungin et al 1999;Jacobson et al 2003;van Soest et al 2006;Reimer and Bytzer, 2009;Lødrup et al 2014;Haastrup et al 2014]. …”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies date several years back, have clustered PPI use with use of histamine type-2 receptor antagonists (H2RA) and were not carried out in a nationwide setting. Furthermore, the studies applied different definitions of long-term use, based on either duration of therapy or used defined daily doses (DDDs) per year, without taking both parameters into account [Hungin et al 1999;Jacobson et al 2003;van Soest et al 2006;Reimer and Bytzer, 2009;Lødrup et al 2014;Haastrup et al 2014]. …”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands, 21% of PPI prescriptions are given for gastroprotection to non-steroidal anti-inflammatory drug or aspirin users. 3 The use of PPIs is thus increasing and this increase may continue over the coming years for several reasons. Reasons include the further rise in the prevalence of GORD and the availability of over the counter and generic PPIs.…”
mentioning
confidence: 99%
“…The majority of these patients use a PPI for a short period, more than 50% stop within the first year of treatment, but approximately one third continue for more than two years. 3 Hence our experience of maintenance therapy with PPIs is now 22 years of continuous treatment, in particular in patients with severe reflux disease. Given the high incidence of acid related disorders and the excellent efficacy of PPIs for the treatment of these conditions, the safety of long term PPI treatment is very relevant.…”
mentioning
confidence: 99%
“…As PPIs have become commonly 29 used for long-term maintenance, concerns have been raised about the safety of such use 6 . 30 Studies have showed that PPI use is associated with malabsorption of vitamins and 31 minerals 7,8 , an increased risk of infections, such as pneumonia 9 and enteric infection 10 , and 32 an increased fracture risk 11,12 . These potential side effects can be minimized through 33 appropriate prescription practices in terms of stepping down the dose or stopping long-term 34 treatment altogether.…”
mentioning
confidence: 99%